Targeting the DNA damage response for cancer therapy - Powell, Simon N.; Bindra, Ranjit S. (DNA repair, 2009)
Human tumors frequently have defects in the maintenance of genomic integrity, which involve a loss of the appropriate response to DNA damage. These pathways of genome integrity include key proteins involved in cell cycle checkpoints, histone modifications, and DNA repair. In this review, we discuss opportunities for therapeutic intervention by exploiting these defects, with an emphasis on those processes which are primarily associated with the repair of double-strand breaks. As these defects are specific to tumor cells, the development of new anti-cancer agents targeting these pathways may have an enhanced therapeutic window, with limited normal tissue toxicity.